Modified Activated Carbon as Selective Solid-Phase Extractant Used for Determination of Au(III), Pd(II) and Pt(IV) by ICP-OES - Liu, Xuqiang (Asian Journal of Chemistry, 2014)
A new solid-phase extractant was synthesized by immobilizing N-aminopropyl-(3,4,5-trihydroxy)benzamide on activated carbon for separation/preconcentration trace of Au(III), Pd(II) and Pt(IV) ions prior to the measurement by inductively coupled plasma optical emission spectrometry (ICP-OES). Different variables that can affect the adsorption of Au(III), Pd(II) and Pt(IV) were optimized including acidity, sample flow rate, volume, elution conditions and potentially interfering ions. The optimal pH value was 2. The adsorption capacity of the material was 195.7, 95.1 and 99.3 mg g-1 for Au(III), Pd(II) and Pt(IV), respectively. Then the adsorbed ions were quantitatively eluted by 4 mL of 3 mol L-1 HCl-6 % CS(NH2)2 solution. The presence of several interfering ions, which existed in high excess, did not interfere in both separation and determination of the noble ions. The detection limit of the method (3s) was 7, 11 and 6 ng mL-1 for Au(III), Pd(II) and Pt(IV), respectively. The relative standard deviation (RSD) in optimum conditions was less than 3 % (n = 11). The developed method has been successfully applied to the preconcentration and determination of Au(III), Pd(II) and Pt(IV) in actual samples.